2013
DOI: 10.1159/000351240
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in Combination with Capecitabine plus Irinotecan as First-Line Therapy in Metastatic Colorectal Cancer: A Pooled Analysis of 2 Phase II Trials

Abstract: Background: Although phase III studies have investigated the effect of adding bevacizumab to the 3-weekly capecitabine plus irinotecan (XELIRI) combination in the first-line treatment of metastatic colorectal cancer (mCRC), no phase III studies investigating the effects of adding bevacizumab to biweekly XELIRI have been published. Patients and Methods: A retrospective pooled analysis of 2 single-arm phase II studies was performed. Previously untreated patients with mCRC received irinotecan 175 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Several studies have evaluated biweekly XELIRI regimens. 26 28 A phase II trial of a biweekly XELIRI regimen (capecitabine 2,000 mg/m 2 on days 2–8 plus irinotecan 175 mg/m 2 on day 1, every 2 weeks) obtained an objective response rate of 32%, a median time to progression of 9 months, and a median OS of 19.2 months. 27 The same regimen plus BV was evaluated in another phase II trial, which obtained a response rate of 67%, a median PFS of 12.3 months (95% CI, 6.5–18.1 months), and an OS of 23.7 months (95% CI, 16.7–30.6 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated biweekly XELIRI regimens. 26 28 A phase II trial of a biweekly XELIRI regimen (capecitabine 2,000 mg/m 2 on days 2–8 plus irinotecan 175 mg/m 2 on day 1, every 2 weeks) obtained an objective response rate of 32%, a median time to progression of 9 months, and a median OS of 19.2 months. 27 The same regimen plus BV was evaluated in another phase II trial, which obtained a response rate of 67%, a median PFS of 12.3 months (95% CI, 6.5–18.1 months), and an OS of 23.7 months (95% CI, 16.7–30.6 months).…”
Section: Discussionmentioning
confidence: 99%
“…The planned dose intensity of irinotecan in this study (90 mg/m 2 /week) was equal to or higher than that used in previously reported biweekly XELIRI (87.5 mg/m 2 /week) or triweekly XELIRI (66.7 mg/m 2 /week) regimens, although these studies treated patients in a first-line setting. 23 , 26 As for capecitabine, the planned dose intensity was similar to that used in these previous studies. As for safety, the incidences of severe diarrhea, neutropenia, and hand–foot syndrome were acceptable despite the higher dose of irinotecan.…”
Section: Discussionmentioning
confidence: 99%
“…52 CAPIRI plus bevacizumab had an acceptable tolerability profile. [51][52][53] First-line capecitabine plus cetuximab was evaluated in elderly patients (70 years or older) with advanced CRC in a phase II trial. In patients with wild-type KRAS, capecitabine plus cetuximab combination was associated with a response rate of 48.3% and a median PFS of 8.4 months.…”
Section: Capecitabinementioning
confidence: 99%
“…5153 The addition of bevacizumab improved PFS, but not OS. 52 CAPIRI plus bevacizumab had an acceptable tolerability profile. 5153…”
Section: Oral Fluoropyrimidinesmentioning
confidence: 99%
See 1 more Smart Citation